The ethno-techno-conservation approach in the utilization of Black Fruit (Haplolobus sp.) by the Wandamen ethnic of Papua, Indonesia - ANTONI UNGIRWALU; SAN AFRI AWANG; PRIYONO SURYANTO; AHMAD MARYUDI (Society for Indonesian Biodiversity, 2017)
Ungirwalu A, Awang SA, Suryanto P, Maryudi A. 2017. The ethno-techno-conservation approach in the utilization of Black Fruit (Haplolobus sp.) by the Wandamen people of Papua, Indonesia. Biodiversitas 18: 1336-1343. Identities and cultures are developed by societies through interaction with their environments. In caring for and using their environment, ecological knowledge is created. Deep knowledge of sustainable utilization and conservation of forest resources exist in Papua, but this traditional wisdom is poorly reflected in scientific literature. Such knowledge includes for example the adaptive traditional management of Black Fruit trees (Haplolobus sp.) by the Wandamen people of Papua, which is the subject of the case study reported in this paper. Our research focused on developing an understanding of how local knowledge about utilization, conservation, and protection of Black Fruit was constructed over time. It employed ethnoecology as the analytical lens. The study was conducted in Teluk Wondama District, West Papua. We found that the adaptive resource management of Black Fruit by the Wandamen is based on an approach which we have called â€œethnotechno- conservationâ€. This approach is an attitude of mind by which Wandamen communities manage their Black Fruit trees to meet the dual goals of fulfilling subsistence needs and conserving the resource. This adaptive strategy has evolved over time as a response to the dynamics of the environment and exemplifies the co-evolution of culture and environment that is a defining feature of the world we all inhabit. The traditional concepts and knowledge of the Wandaman elaborate conservation values in the utilization of the Black Fruit. These adaptive concepts and knowledge are codified in their beliefs, myths, and handed-down wisdom.